Surface Structures Involved in Plant Stomata and Leaf Colonization by Shiga-Toxigenic Escherichia Coli O157:H7 - Saldaña, Zeus; Sánchez, Ethel; Xicohtencatl-Cortes, Juan; Puente, Jose L.; Giron, Jorge A. (Frontiers in Microbiology, 2011)
Shiga-toxigenic Escherichia coli (STEC) O157:H7 uses a myriad of surface adhesive appendages including pili, flagella, and the type 3 secretion system (T3SS) to adhere to and inflict damage to the human gut mucosa. Consumption of contaminated ground beef, milk, juices, water or leafy greens has been associated with outbreaks of diarrheal disease in humans due to STEC. The aim of this study was to investigate which of the known STEC O157:H7 adherence factors mediate colonization of baby spinach leaves and where the bacteria reside within tainted leaves. We found that STEC O157:H7 colonizes baby spinach leaves through the coordinated production of curli, the E. coli common pilus (ECP), hemorrhagic coli type 4 pilus (HCP), flagella, and T3SS. Electron microscopy analysis of tainted leaves revealed STEC bacteria in the internal cavity of the stomata, in intercellular spaces, and within vascular tissue (xylem and phloem), where the bacteria were protected from the bactericidal effect of gentamicin, sodium hypochlorite or ozonated water treatments. We confirmed that the T3S escN mutant showed a reduced number of bacteria within the stomata suggesting that T3S is required for the successful colonization of leaves. In agreement, non-pathogenic E. coli K-12 strain DH5α transformed with a plasmid carrying the LEE pathogenicity island, harboring the T3SS and effector genes, internalized into stomata more efficiently than without the LEE. This study highlights a role for pili, flagella, and T3SS in the interaction of STEC with spinach leaves. Colonization of plant stomata and internal tissues may constitute a strategy by which STEC survives in a nutrient-rich microenvironment protected from external foes and may be a potential source for human infection.